2005
DOI: 10.1080/02652030500197680
|View full text |Cite
|
Sign up to set email alerts
|

Determination of 3-chloropropane-1,2-diol as its 1,3-dioxolane derivative at the μg kg−1level: Application to a wide range of foods

Abstract: This paper reports the application of a GC/MS method for the quantification of 3-chloropropane-1,2-diol (3-MCPD) at low microg kg-1 levels through the determination of its 1,3-dioxolane derivative to a wide range of foodstuffs. The proposed protocol is based on the methods generally performed in control laboratories. The two main stages of the method - the solid-phase extraction and the purification of the derivatives - have been optimized. The within-laboratory reproducibility meets the official performance c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 25 publications
2
13
0
1
Order By: Relevance
“…The results showed that 20% MTBE was optimal for the extraction of 3‐MCPD and its esters from the oil. These results were consistent with previous findings that concentrations of ethyl acetate and MTBE played an important role in the extraction of 3‐MCPD and its esters from oil and fat‐based matrices . It indicates that it is necessary to take into account the polarity of organic solvents involved in the dilution and transesterification of lipophilic 3‐MCPD esters and hydrophilic 3‐MCPD.…”
Section: Resultssupporting
confidence: 92%
“…The results showed that 20% MTBE was optimal for the extraction of 3‐MCPD and its esters from the oil. These results were consistent with previous findings that concentrations of ethyl acetate and MTBE played an important role in the extraction of 3‐MCPD and its esters from oil and fat‐based matrices . It indicates that it is necessary to take into account the polarity of organic solvents involved in the dilution and transesterification of lipophilic 3‐MCPD esters and hydrophilic 3‐MCPD.…”
Section: Resultssupporting
confidence: 92%
“…4a). However Retho and Blanchard (2005) suggested that the derivatisation reaction with HFBI exhibits poor selectivity because HFBI may react with nucleophilic molecules. The mass spectrum of the obtained derivative displays a low intensity signal in the region characteristic for specific ions, which may indicate insufficient (incomplete) derivatisation.…”
Section: Analytical Procedures Used For Determination Of 3-mcpd In Fomentioning
confidence: 99%
“…Other filter agents and sorbents, such as Celite (diatomaceous earth) and florisil, used in previously published studies (Rétho and Blanchard 2005;Racamonde et al 2011), were also tested in our experiment. However, in our experiment all materials were used as bulk sorbents, being added to the extracts.…”
Section: Optimization Of Sample Preparation Methodsmentioning
confidence: 99%
“…The 3-MCPD was detected in coffee and coffee surrogates at levels up to 759 lg kg -1 (Kurzrock and Speer 2007 The conventional sample preparation method for 3-MCPD consists of extraction with various ethers, ethyl acetate, dichloromethane, or mixture acetone with hexane. Clean-up of the extract is conducted mainly with a column chromatography loaded with alumina, diatomaceous earth or an Extrelut column, followed by derivatisation mostly with PBA (phenylboronic acid), heptafluorobutyrylimidazole (HFBI) or heptafluorobutyric acid anhydride (HFBA) and with a final detection by gas chromatography (Rétho and Blanchard 2005;Baer et al 2010;Racamonde et al 2011). Many of these procedures do not perform well in more complex and difficult matrixes such as coffee or coffee substitutes, due to the presence of undesirable co-extractives that produce interferences affecting chromatographic analysis.…”
Section: Introductionmentioning
confidence: 99%